Seismic Shot Point Navigation Data from offshore Cape Hatteras to the Mid-Atlantic Ridge acquired during R/V Gulf Seal expedition GS1974 (1974) (IEDA: Marine-Geo Digital Library, 2014)
This data set was acquired with a Multi-Channel Seismic system during Gulf Seal expedition GS1974 conducted in 1974 (Chief Scientist: Dr. John Grow; Investigator(s): Dr. John Grow and Dr. Rudi G. Markl). These data files are of Text File (ASCII) format and include Seismic Shot Time Navigation data and were processed after data collection. Data were acquired as part of the project(s): International Phase of Ocean Drilling (IPOD) Site Survey, and funding was provided by NSF grant(s): UC-NSF-C482-2 scope F.